Real-world use of ustekinumab therapeutic drug monitoring in moderate to severe psoriasis - Elberdín, Laida; Fernández-Torres, Rosa M.; Mateos, María; Outeda, María; Blanco, Eva; Gómez-Besteiro, María I.; Martín-Herranz, Isabel; Fonseca, Eduardo (Frontiers in Medicine, 2022)
Introduction There is growing evidence that therapeutic drug monitoring of biologic therapy is beneficial in psoriatic patients. With respect to ustekinumab, the available evidence has not shown any relationship yet. The objective of this study is to identify correlations among ustekinumab trough concentrations, anti-ustekinumab antibodies and clinical response in moderate-to-severe plaque psoriasis patients, in a real-world setting. Methods Observational prospective follow-up study in psoriatic patients treated with ustekinumab. Patients were classified in optimal (PASI ≤ 3) and suboptimal responders (PASI > 3). Mann–Whitney U test and Spearman’s rank correlation coefficient were used. Receiver-operator characteristic curve analysis was performed to identify ustekinumab concentration cut-off to achieve optimal response. A p-value < 0.05 was considered statistically significant. Results A total of 59 patients were included. Forty-eight patients (81.4%) corresponded to optimal responders and 11 (18.6%) to suboptimal responders. There was significant difference to ustekinumab concentrations: 0.7 μg/mL (range <0.1–1.8) vs. 0.4 μg/mL (range <0.1–0.8) respectively (p = 0.007). Positive correlation between ustekinumab concentration and psoriasis area and severity index (PASI) value was detected (p = 0.009). A cut-off value of 0.6 μg/mL ustekinumab concentration was found to achieve clinical response. Anti-ustekinumab antibodies were detected in 2 (3.4%) samples, both suboptimal responders. Conclusion A positive correlation exits between ustekinumab concentration and clinical response (optimal response PASI values ≤ 3) in blood draws performed before drug administration. The measurement of anti-ustekinumab antibodies could be considered in treatment failure.